Membangun Brand Image Reksadana Syariah Di Indonesia - Taufiqur Rahman (Institut Keislaman Abdullah Faqih Gresik, 2015)
Mutual funds-called Reksadana- is a container used to collect funds from investors to be invested in the securities portfolio by investment manager who has received permission from Badan Pengawas Penanaman Modal (BAPEPAM).The operational principle which is used in Islamic mutual funds is the principle of mudarabah or Qiradh. The principle of Mudharabah or Qiradh is interpreted as a bond or a system where a person gives his wealth to another person to be managed with the provision that the profits earned from the management of the results were split between the two parties in accordance with the terms agreed upon by both parties.We hope that the mutual Shariah will find herself back. And with presence will make an investment alternative in a Islamic principle capital market and provide the benefit and welfare for Muslims in Indonesia